2016
DOI: 10.1038/srep36561
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Lkb1 in adult mice results in body weight reduction and lethality

Abstract: Liver kinase B1 (Lkb1) plays crucial roles in development, metabolism and survival. As constitutive knockout of Lkb1 in mice leads to embryonic lethality, whether Lkb1 is required for the growth and survival of adult mice is unclear. Here we address this question using a tamoxifen-inducible Lkb1 knockout (KO) mouse model: Rosa26-CreER: Lkb1flox/flox (abbreviated as Rosa-Lkb1). The Rosa-Lkb1 mice exhibited body weight reduction and died within 6 weeks after tamoxifen induction. The body weight reduction was due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
7
16
0
Order By: Relevance
“…In seeking to account for this, we speculated that a defect in metabolism was a likely source of the growth retardation in the mice. To examine this possibility, we chose to focus on the AMPK-signaling pathway, because it has previously been reported that disruption of LKB1-AMPK-mTOR signaling results in a reduction in mouse body weight, analogous to our observations (14,15). The decreased body weight in the mutant animals corresponded with a reduction in food intake by the animals (Fig.…”
Section: Nischarin Lrr-deletion Improves Energy Balance Glucose and Isupporting
confidence: 66%
“…In seeking to account for this, we speculated that a defect in metabolism was a likely source of the growth retardation in the mice. To examine this possibility, we chose to focus on the AMPK-signaling pathway, because it has previously been reported that disruption of LKB1-AMPK-mTOR signaling results in a reduction in mouse body weight, analogous to our observations (14,15). The decreased body weight in the mutant animals corresponded with a reduction in food intake by the animals (Fig.…”
Section: Nischarin Lrr-deletion Improves Energy Balance Glucose and Isupporting
confidence: 66%
“…It has previously been shown that mice with systemic autophagy ablation have a life span of 2-3 months and the mortality is due to initial Streptococcus infection and eventual neurodegeneration (16). Whereas, adult mice with whole-body Lkb1 deletion survive for up to 6 weeks (23). Given that both Lkb1 signaling and autophagy pathway regulate cellular homeostasis (12,16,18,24), we hypothesize that upregulation of autophagy in Lkb1-deficient mice might compensate for the acute Lkb1 loss to maintain energy homeostasis for mouse survival.…”
Section: Interaction Of Lkb1 and Autophagy Is Required For Adult Mousmentioning
confidence: 99%
“…AMPK is a conserved serine/threonine kinase that functions in the regulation of energy metabolism [16]. A previous study showed that LKB1 is necessary for white adipose tissue (WAT) growth and differentiation [17]. Moreover, the LKB1/AMPK signaling pathway negatively regulates WAT [18].…”
Section: Introductionmentioning
confidence: 99%